Influence of assisted POE (predict, observe, explain) model diorama on students' understanding of science concepts at SD Negeri Pringapus 01 - Nari, Hariyati; Yuni Purwanti, Kartika (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
This research aims to determine the difference in the use of the POE (Predict, Observe, Explain) model assisted by dioramas on understanding concepts, to find out the effect of using the POE (Predict, Observe, Explain) model assisted by dioramas on understanding concepts. This research was conducted at SDN Pringapus 01. This research uses a quantitative approach with a quasi-experimental method. The sample determination in this research was purposive sampling. The population in this study were students at SDN Pringapus 01. The samples taken in this study were class IV at SDN Pringapus 01. Where class IV A was the experimental class and class IV B was the control class. With data collection techniques using science description question sheets, observation sheets and questionnaires. The data analysis techniques used are normality tests, homogeneity tests and hypothesis tests in the form of paired sample t-tests and simple linear regression tests. The research results show (1) there is an influence of using the POE (Predict, Observe, Explain) model assisted by dioramas on increasing understanding of concepts. This is proven by a significant value of 0.000 <0.05. (2) There is a significant difference between learning using the POE (Predict, Observe, Explain) model assisted by dioramas towards understanding science concepts. This is also proven by the significance results of 0.000 <0.05. The conclusion from this research is that the POE (Predict, Observe, Explain) model assisted by dioramas has an influence in increasing students' understanding of science concepts.